Vax Populi: The Social Costs of Online Vaccine Skepticism - Matilde Giaccherini; Joanna Kopinska; Gabriele Rovigatti (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper quantifies the impact of online vaccine skepticism on pediatric vaccine uptake and health outcomes. We propose a novel methodology that combines Natural Language Processing and an instrumental variable strategy that leverages the intransitivity of the social network's connections. By matching the universe of Italian vaccine-related tweets for 2013-2018 with vaccine coverage and preventable hospitalizations at the municipality level, we find that a 10pp increase in anti-vaccine sentiment causes i) a 0.43pp decrease in coverage of the Measles-Mumps-Rubella vaccine, ii) additional 2.1 hospitalizations among vulnerable populations per 100,000 residents, and iii) an 11% increase in the relevant healthcare expenses, equivalent to 7,311 euros. Drawing on the results of a simulated model, we further show the importance of targeted interventions to counter misinformation and improve vaccine uptake.
Keywords: I18; D85; L82; C81; 330; social network; Twitter; vaccines; controversialness; polarization; text analysis